(untitled) (Universal International Scientific Journal, 2026)
This article is aimed at highlighting the methodological aspects of developing the speech of primary school students. Attention is paid to the formation of such important aspects as pronunciation, grammar, and enrichment of speech in the speech activity of students. It is also emphasized the importance of forming a culture of communication, adherence to the norms of the literary language, and a culture of speech based on the rules of etiquette.